Stigting van die Vaalhartsbesproeiingskema as heenkome vir hawelose armblankes - R.T.J. Lombard (Contree)
Owing to the economic crisis and drought of the early 1930s, the government decided to begin with the construction of a scheme which would provide a means of livelihood for thousands of poor whites. In addition to a large storage dam (Vaal Dam) which was to ensure a sufficient supply of water to the scheme, a diversion weir (Vaalharts Dam) was also constructed on the Vaal River. By means of its network of concrete canals running across the entire Hans Valley up to Taung, this system could irrigate 1 250 plots of approximately 25 hectares each. In April 1938 the first 27 farmers were settled on the scheme, and by the end of 1940 this number had risen to 360. After the Second World War, returning servicemen were also resettled there. Although the settlers initially struggled to make a living, they eventually succeeded in becoming independent farmers, able to purchase their own small plots.